Schubert s dramatic Lieder to Poems by Goethe: Technical and interpretive decision-making from a lyric baritone s perspective - Lodewyk, Aubrey (College of Music, 2025)
This study explores the technical and interpretive challenges that a lyric baritone experiences when performing Schubert's dramatic Lieder set to Goethe's poems. Schubert's dramatic Lieder incorporates elements found in theatrical works, such as narrators, personae, recitatives and declamation, which pose interpretive challenges for the lyric baritone (Hirsch 1993. 2). The Lieder also consists of wide vocal ranges, sections with high tessitura, wide interval leaps and long phrases, each presenting notable technical challenges for the lyric baritone (Hirsch 1993. 2). Related technical aspects, specifically vowel modification in the zona di passaggio, breath management, and changes in vocal timbre, are also challenges that the lyric baritone must address, which this study examines (Brown 2018). Biographical knowledge of the lives and work of the composer and the poet is crucial for interpreting and performing their work (Miller 1999, 3). Therefore, overviews of Schubert and Goethe are provided, and a contextual examination is provided to define the dramatic elements within a Lied. This study adopts a qualitative research approach and interpretivist paradigm that combines practice-led and autoethnographic methods within a hermeneutic research design to interpret the Lieder. This combined approach, including reflexivity based on my own experience as a lyric baritone performing the Lieder, assists in analysing and interpreting the text of Schubert's dramatic Lieder set to Goethe's poems. The study identifies technical and interpretive challenges relating to the inherent dramatic elements in the words and the music and explores solutions to these challenges for the lyric baritone.